An assessment of GLOBOCAN methods for deriving national estimates of cancer incidence - Antoni, Sebastien (Bull World Health Organ, 2016)
OBJECTIVE: To assess the validity of the GLOBOCAN methods for deriving national estimates of cancer incidence. METHODS: We obtained incidence and mortality data from Norway by region, year of diagnosis, cancer site, sex and 5-year age group for the period 1983–2012 from the NORDCAN database. Estimates for the year 2010 were derived using nine different methods from GLOBOCAN. These included the projection of national historical rates, the use of regional proxies and the combination of national mortality data with mortality to incidence ratios or relative survival proportions. We then compared the national estimates with recorded cancer incidence data. FINDINGS: Differences between the estimates derived using different methods varied by cancer site and sex. Methods based on projections performed better where major changes in recent trends were absent. Methods based on mortality data performed less well for cancers associated with small numbers of deaths and for cancers detectable by screening. In countries with longstanding cancer registries of high quality, regional-based, or trends-based incidence estimates perform reasonably well in comparison with recorded incidence. CONCLUSION: Although the performance of the GLOBOCAN methods varies by cancer site and sex in this study, the results emphasize a need for more high-quality population-based cancer registries – either regional or, where practical and feasible, national registries – to describe cancer patterns and trends for planning cancer control priorities.